Ensaio nutricional de Pereskia spp.: hortaliça não convencional - Silveira, Melissa Guimarães (2015)
The ora-pro-nobis is an unconventional vegetable of easy to grow and a complementary source to combat nutritional deficiencies and chronic diseases, high nutritional and bioactive value. However, like other leafy vegetables, antinutritional constitution is worrying, it must be known and where possible reduced to achieve their full functional potential in humans. The physicochemical characterization of two edible species Pereskia aculeata, in particular the profile of predominant organic acids and aminoacid, by chromatographic methods as well as the stability of all these compounds against ways and for different cooking was investigated and the results evaluated using statistical techniques Univariate and multivariate. The leaves of the species grandifolia Pereskia Haworth and Pereskia aculeata Miller were collected in the Medicinal Garden at the Federal University of Lavras, Minas Gerais, during the month of September 2014 and submitted to proximate analysis, chlorophyll and vitamin C, mineral fibers (enzyme-gravimetric method), total phenolics, total antioxidant activity, assessed by spectrophotometric methods specific for aqueous and oily solutions and antinutritional (oxalic acid, tannins, nitrates and trypsin inhibitor by enzyme assay). Samples of ora-pro-nobis presented rich in protein, fiber, mostly insoluble, and minerals like iron and calcium. The two species showed different chemical behavior under heat treatment and, by the techniques of principal component analysis and multidimensional scaling were well broken down. The cooking process was not impressive reduction of the metal ions calcium and iron, while the remainder of the minerals and vitamin C were slightly trapped in leaves, particularly those maintained under heat for a longer time. In terms of increased antioxidant action, the cooking was beneficial to the species P. aculeata, with the highest retention of phenolic antioxidant in the leaves and the free radical trapping methods DPPH and co-oxidation of β- carotene system. Among the antinutritional factors analyzed, regardless of the initial value observed in nitrate raw sheets, the heat treatment was able to reduce the content of antinutritional to lower values, like in amabas species. Inhibition of the enzyme trypsin was significantly reduced after 1 minute of cooking while maintaining the inhibitory activity keep the anti-nutritional character of leaf extracts. A response surface analysis suggested that the antinutritional complexing minerals, tannins and oxalic acid, showed high retention in coccionadas leaves of both types, due to interaction with mineral whose content is high in these leafy, zinc, in P. grandifolia and iron, in P. aculeata. The recommendation of how best to prepare and benefit consumption varies according to the species studied, and the results support the assertion that the changes, especially in anti-nutritional content of these vegetables and other leafy with similar nutritional composition subjected to the same conditions of preparation, needs further investigation before their human ingestion recommendation.